Beyond Clinical Intuition: Quantitative Mortality Prediction in Blunt Thoracic Trauma using the Thoracic Trauma Severity Score (TTSS) - Harief Seamaladi; Aswin Nugraha; Erial Bahar (Sriwijaya Journal of Surgery, 2025)
Introduction: Blunt thoracic trauma is a leading cause of significant morbidity and mortality, particularly in younger populations. Accurate and early prediction of mortality is crucial for guiding clinical management and resource allocation. This study aimed to move beyond subjective clinical assessment by evaluating the accuracy of the Thoracic Trauma Severity Score (TTSS) as an objective, quantitative tool for predicting in-hospital mortality in patients with blunt thoracic trauma in a specific regional trauma center. Methods: A retrospective cohort study was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Data from 38 patients admitted with blunt thoracic trauma between January 2023 and January 2025 were analyzed. The TTSS was calculated for each patient based on five parameters: age, number of rib fractures, presence of bilateral rib fractures, extent of pulmonary contusion (assessed by chest X-ray), and the PaO2​/FiO2​ ratio (from arterial blood gas analysis). The primary outcome was in-hospital mortality. Receiver Operating Characteristic (ROC) curve analysis was used to determine the predictive accuracy of the TTSS, including the Area Under the Curve (AUC), sensitivity, specificity, and optimal cut-off value. Bivariate analysis using the chi-square test was performed. Results: Of the 38 patients, 76.3% (n=29) were male. The mortality rate was 15.8% (n=6). The ROC curve analysis for TTSS in predicting mortality yielded an AUC of 0.727 (95% CI: 0.447–1.000; p = 0.082). At an optimal cut-off value of 10.5, the TTSS demonstrated a sensitivity of 66.6% and a specificity of 71.8% for mortality prediction. Patients with TTSS >7 had a significantly higher proportion of mortality (83% of deaths occurred in this group) compared to those with TTSS $≤$7. Conclusion: The Thoracic Trauma Severity Score (TTSS) showed fair predictive accuracy for in-hospital mortality in patients with blunt thoracic trauma in this study setting. While demonstrating reasonable sensitivity at a cut-off of 10.5, its specificity was also moderate. The TTSS can serve as a useful quantitative adjunct to clinical judgment, aiding in the early identification of patients at higher risk, though its limitations, particularly the modest specificity and non-significant p-value for AUC in this cohort, warrant cautious interpretation and highlight the need for further validation in larger, multicenter studies.